DNA BASED GENDER IDENTIFICATION OF MEAT SAMPLES - M. Iqbal; W. Shehzad1; M. Imran; M. Y. Zahoor; W. A. Khan; M. I. Rashid; K. Ashraf; H. Rehman; M. S. Saleem; A. Nadeem (Journal of Animal and Plant Sciences, 2020)
Meat is an important component of our diet. Male meat is exclusively preferred for consumption. In order to control the quality of suppliers the identification of the meat gender is important for meat processors. The DNA based methods have proved, to be efficient for gender identification. Females (bovine and ovine) are used for reproduction and are normally slaughtered only when older, which lead to increase in length and rigidity of muscle fibers resulting in tougher meat of lower quality. To enable detection of male bovine meat samples, a PCR-assay was designed in the present study. The Amelogenin gene located on X and Y-chromosome has proved to be a good marker for gender identification even in cooked meat samples. A pair of primers was designed based on AMEL-X and AMEL-Y genes which would be able to identify animal gender of bovine and ovine meat samples. The accuracy and specificity of the primers was assessed using DNA template extracted from bovine and ovine meat samples of known gender. Established method was applied to 180 bovine and ovine meat samples. PCR products of meat samples after electrophoresis showed two bands (250, 180-bp) for male DNA sample while only single band (250bp) for female DNA Sample. Result shows that the PCR assay based on the Amelogenin gene is reliable for gender determination in meat. This technique is also of practical utility in biodiversity assessment in non-invasive studies. Gender identification plays an important economic role in animal production industries where females are requisite for the dairy industry while males are preferred for beef production.
Keywords: Amelogenin; gender identification; non-invasive